Technologies and factors affecting bioethanol fermentation and its commercialization - Ezea, Ifeanyi Boniface (Archives of Ecotoxicology, 2023)
Fossil fuels are a major contributor to climate change and environmental pollution, and as the demand for energy production increases, alternative sources are becoming more attractive. Bioethanol reduce reliance on fossil fuels and can be compatible with the existing fleet of internal combustion engines. Bioethanol is typically produced via microbial fermentation of fermentable sugars. Traditional feedstocks (first- generation) include cereal grains, sugar cane, and sugar beets. However, due to concerns regarding food sustainability, lignocellulosic (second-generation) and algal biomass (third-generation) feedstocks have been investigated. Technologies such as Simultaneous Saccharification and Fermentation (SSF), Separate enzymatic Hydrolysis and Fermentation (SHF) and Fed- batch Fermentation for bioethanol hold tremendous potential for the production of bioethanol. The aim of this review focuses on the technologies and factors affecting bioethanol production and its commercialization.